Decarburization of ferrochrome and high alloy steels with optimized gas and slag phases towards improved Cr retention - Wang H.; Nzotta M.M.; Teng L.; Seetharaman S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Chromium is a high value metal and the retention of the same during the refining of high carbon ferrochrome as well as high alloy steel has significant economic and environmental impacts. The loss of chromium during the decarburization is generally minimized using argon-oxygen mixtures thereby reducing the oxygen partial pressure (PO2) of the oxidant gas. In the current study, experiments were carried out in an induction furnace and CO2 was introduced with the view to partly reduce PO2 and partly as an oxidizer. During these experiments, the decarburization of molten Cr-alloy was conducted using pure O2, pure CO2 or O2+CO2 mixtures. The results demonstrated that the Cr loss can be minimized under CO2 introduction. The kinetic analysis showed that the mass transfer is effective due to the production of 2CO gas molecules from one CO2 molecule during the reaction which will improve the stirring of the bath. Besides, CO2 reacts with carbon in melt is an endothermic reaction, introduction of CO2 could be a cooler during the refining process, hence the temperature could be controlled by controlling the diluting gas amount, in this case, the over heat of bath refractory could be prevented and the lifetime of refractory could be extended.